Increasing Customer Loyalty Based on Perceived Ease of Use, Brand Equity, and Product Differentiation - Aryono, Muhamad Puji; Priyambodo, Syahtri Wardana (Faculty of Economics and Business UNTAG Semarang, 2024)
This research aims to determine the influence of perceived ease of use, brand equity, and product differentiation on Tokopedia customer loyalty. The sample for this research was students from the Faculty of Economics and Business, Universitas 17 Agustus 1945 Semarang, totaling 88 students. The data analysis used multiple linear regression analysis. The results show that perceived ease of use does not affect customer loyalty, brand equity has no effect on customer loyalty, and product differentiation has an effect on customer loyalty. The influence of perceived ease of use and brand equity is not significant on customer loyalty because this influence varies depending on the context, industry, and specific characteristics of a particular product or service.